2021
DOI: 10.1002/essoar.10506309.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of Transient-Large-Amplitude Geomagnetic Perturbation Events

Abstract: Space weather events occur due to the interaction of active solar wind with near-Earth space, activating magnetohydrodynamic (MHD) and electromagnetic transfer processes that propagate throughout the magnetosphere-ionosphere (M-I) system down to the surface of Earth. Perhaps the most critical concern regarding space weather is the threat of large geomagnetically induced currents (GIC) to technological infrastructure on Earth. Flowing through man-made conductors on Earth like railways, pipelines and power grids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…(2001) and Viljanen and Tanskanen (2011), >360 nT/min in McCuen et al. (2021), and >500 nT/min in Schillings et al. (2021).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…(2001) and Viljanen and Tanskanen (2011), >360 nT/min in McCuen et al. (2021), and >500 nT/min in Schillings et al. (2021).…”
Section: Introductionmentioning
confidence: 91%
“…Most of the intervals occurred in the pre‐midnight and midnight sectors. The dusk sector has the least number of events possibly because the occurrence rate of large dB/dt is lower than that in the nighttime sector (McCuen et al., 2021; Schillings et al., 2021; Viljanen & Tanskanen, 2011; Viljanen et al., 2001). Available auroral observations are also fewer because the proximity to the solar terminator means that the auroral observations are more subject to sunlight contamination than those in the nighttime sector.…”
Section: Statisticsmentioning
confidence: 99%
“…However, these second‐scale magnetic field changes may be especially important in understanding small‐scale dynamics of space weather events. While magnetic disturbances in this Pi 1–2 frequency range do not cause GICs directly, they have been found to occur prior to and/or during some GIC‐capable space weather events, nighttime MPEs in particular (McCuen et al., 2021).…”
Section: Introductionmentioning
confidence: 98%
“…McCuen et al. (2021) found that TLA d B /d t intervals identified in 2015 often occurred in the pre‐midnight sector (magnetic local time), 30 min after a substorm onset and in association to many of the most extreme nighttime MPEs. Of 175 MPEs at four Magnetometer Array for Cusp and Cleft Studies (MACCS) stations in 2015 (IGL, RBY, PGG, and CDR), nearly half of the 52 largest events (maximum d B /d t values greater than 10 nT/s) had associated TLA d B /d t intervals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation